Penguatan Ekonomi Masyarakat Melalui Penanaman Pohon dan Aksi Nyata Peduli Lingkungan - Winta Panimba; Yusuf L. Limbongan; Lantana Dioren Rumpa; Asyer Frienra Pratama Roba (Pusat Riset dan Inovasi Nasional, 2026)
The Thematic Community Service Program (KKN-T) by students of the Indonesian Christian University of Toraja in Tondon Langi Village, Tondon District, focuses on reforestation as an effort to preserve the environment while strengthening the community's economy. This initiative is driven by the presence of unused land and the community's road access, which is often blocked due to landslides, hindering their access to livelihood locations like gardens and rice fields. Additionally, there is a lack of awareness about the economic value of trees. The activities carried out include observation, socialization, and the planting of teak and mahogany trees, in collaboration with the local community, police, and TNI officers. These efforts aim to foster environmental awareness and highlight the long-term economic benefits of trees. The program not only promotes environmental conservation but also strengthens social bonds through collaboration and cooperation. By involving all stakeholders, this activity seeks to build a greener, more sustainable village, encouraging the community to see trees as a valuable investment for the future.